Soccer fans in shiny sticker shock. Issue 3 (26th May 2021) - Paulden, Tim
Abstract : Sticker packs and albums are part and parcel of the football fan experience. But Dr Tim Paulden and friends found some stickers harder to find than others Abstract : Sticker packs and albums are part and parcel of the football fan experience. But Dr Tim Paulden and friends found some stickers harder to find than others.